I don’t get it. Response difficulties in answering political attitude statements in Voting Advice Applications. - Naomi Kamoen; Bregje Holleman (Survey Research Methods, 2017)
Voting Advice Applications are online tools that provide users with a voting advice based on their answers to a set of political attitude questions. This study investigated to what extent VAA users understand the questions that lead to the voting advice, and what search and response behaviour they expose in case of comprehension difficulties. Two studies were conducted to investigate these issues: a cognitive interviewing study among 60 VAA users during the Dutch municipal elections in the city of Utrecht, and a statistical analysis of all answers provided by 357,858 users who accessed one of the 34 municipal VAAs during these same elections. Results of the two studies show a coherent picture: difficult concepts (e.g., tax names or municipal jargon), geographical locations (e.g., reference to a specific street), and vague quantifying terms (e.g., “more”) all complicate the question. In case of comprehension difficulties, Study 1 shows that VAA users make little effort to solve their problems, for example by looking up difficult terms on the Internet. Instead, they draw inferences about what the question might mean and proceed to answer nonetheless. These are often neutral or no opinion answers, which seems to suggest that the meanings of those options are confounded. In Study 2, however, we found that the choice for either a neutral or no opinion response is not accidental: semantic meaning problems often result in no opinion answers, whereas pragmatic problems are related to neutral responses. We discuss the implications of these findings for survey theory and practice.